Consequences of southward enlargement for EC-Latin American relations - Guido Ashoff (Intereconomics, 1982)
Over the past two decades Latin America, due to both political and economic considerations, has been endeavouring to establish intensive cooperative relations with the European Community. For a variety of reasons this objective has so far only been achieved in part. The Falklands/Malvinas conflict subjected these relations to a serious strain, the results of which cannot as yet be estimated. Another factor, in the longer term, is the European Community's southward enlargement. Latin American assessments of the effects of this diverge: a fear of serious disadvantages to trade on the one hand is matched on the other by the hope that Spain and Portugal will become champions of Latin American interests in the European Community.
Keywords: 330; Integration